Emotional energy, work self-efficacy, and perceived similarity during the Mars 520 study - Solcová, Iva; Gushin, Vadim; Vinokhodova, Alla; Lukavský, Jirí (Aviation, space, and environmental medicine, 2013)
BACKGROUND: The objective of the present research was to study the dynamics of changes in emotional energy, work self-efficacy and perceived similarity in the crew of the Mars 520 experimental study. METHODS: The study comprised six volunteers, all men, between 27-38 yr of age (M = 32.16; SD = 4.99). The Mars 520 experimental study simulated all the elements of the proposed Mars mission that could be ground simulated, i.e., traveling to Mars, orbiting it, landing, and returning to Earth. During the simulation, measures of emotional energy, work self-efficacy, and perceived similarity were repeated every month. The data were analyzed using linear mixed effect models. RESULTS: Emotional energy, work self-efficacy, and perceived similarity gradually increased in the course of the simulation. DISCUSSION: There was no evidence for a so-called third quarter phenomenon (the most strenuous period of group isolation, psychologically, emotionally, and socially) in our data. On the contrary, work self-efficacy, emotional energy, and group cohesion (indexed here by the subject's perceived similarity to others) increased significantly in the course of the simulation, with the latter two variables showing positive growth in the group functioning.
Keywords: Self Efficacy; fyziologická adaptace; interpersonální vztahy; Interpersonal Relations; mužské pohlaví; Confined Spaces; Social Isolation; Ecological Systems, Closed; Adult; sociální izolace; kosmický let; Humans; sebeuplatnění; uzavřené prostory; emoce; Emotions; dospělí; uzavřené ekologické systémy; Space Flight; lidé; Male; Adaptation, Physiological